Efeito do óleo essencial de Citrus Aurantium L. nos níveis de ansiedade em usuários de crack - Chaves Neto, Gabriel (2016)
The chemical dependency today is a widely discussed phenomenon, and among the most destructive drugs stands out the crack. The crack addicts, who seek treatment to dump the drug use, face abstinence – surrounded period of anxiety. With a large number of crack addicts in our country, it is necessary to search for alternative measures that help to reduce anxiety levels. The present study aimed to investigate the clinical anxiolytic potential of Citrus aurantium L. on crack addicts in abstinence. The study was developed with internal users admitted to therapeutic farms in Paraiba, Brazil. The sample consisted of 51 volunteers, who were divided into three groups. To elicit anxiety, were used the Public Speech Simulation (PSS). Physiological measurements was evaluated in the experiment using appropriate equipment, as also psychological measures of anxiety levels, using the State Trait Anxiety Inventory (STAI) and Analog Scale Humo (EAH). The essential oil of Citrus aurantium L. was administered by nebulization. The experiment was developed in unique and individual sessions and consolidated in four stages: (I) Basal (II) Stressor, (III) During and (IV) Final. Data analysis was performed using parametric and non-parametric statistical methods. The results showed that the volunteers of the groups using the OE kept anxiety levels controlled during the PSS, with statistical difference when compared to "control". Volunteers, who used the OE also maintained stable levels of the "discomfort" and "Cognitive Impairment" measured by EAH in moments of realization of PSS. It follows that internal crack users individuals in abstinence have a high trait anxiety, and the EO Citrus aurantium L. nebuliser presented acute anxiolytic effect on internal crack users in abstinence submitted to PSS.